Literature Review Factors Affecting Professional Organizations Leadership, Organizational Communication, Work Motivation and Performance - Gupron, Gupron (International Journal of Advanced Multidisciplinary, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that affect professional organizations, namely: leadership, organizational communication, work motivation, and performance. The results of this research library are that: 1) Leadership has an effect on Professional Organizations; 2) Organizational Communication has an effect on Professional Organizations; 3) Work Motivation has an effect on Professional Organizations; 4) Performance has an effect on Professional Organizations.